Genotyping-by-sequencing-based identification of Arabidopsis pattern recognition receptor RLP32 recognizing proteobacterial translation initiation factor IF1 - Fan, Li; Fröhlich, Katja; Melzer, Eric; Pruitt, Rory N.; Albert, Isabell; Zhang, Lisha; Joe, Anna; Hua, Chenlei; Song, Yanyue; Albert, Markus; Kim, Sang Tae; Weigel, Detlef; et al. (Nature Communications, 2022)
Activation of plant pattern-triggered immunity (PTI) relies on the recognition of microbe-derived structures, termed patterns, through plant-encoded surface-resident pattern recognition receptors (PRRs). We show that proteobacterial translation initiation factor 1 (IF1) triggers PTI in Arabidopsis thaliana and related Brassicaceae species. Unlike for most other immunogenic patterns, IF1 elicitor activity cannot be assigned to a small peptide epitope, suggesting that tertiary fold features are required for IF1 receptor activation. We have deployed natural variation in IF1 sensitivity to identify Arabidopsis leucine-rich repeat (LRR) receptor-like protein 32 (RLP32) as IF1 receptor using a restriction site-associated DNA sequencing approach. RLP32 confers IF1 sensitivity to rlp32 mutants, IF1-insensitive Arabidopsis accessions and IF1-insensitive Nicotiana benthamiana, binds IF1 specifically and forms complexes with LRR receptor kinases SOBIR1 and BAK1 to mediate signaling. Similar to other PRRs, RLP32 confers resistance to Pseudomonas syringae, highlighting an unexpectedly complex array of bacterial pattern sensors within a single plant species.
CRIS-Team Scopus Importer:2022-03-25